A Systematic Literature Review On Social Media Utilisation And Technology Readiness For Enhancing Marketing Capabilities Of Fashion And Tailoring SMEs - Jundian Priyatin; Rina Febriana; Yeni Sesnawati (PT. Anagata Sembagi Education, 2025)
This study presents a systematic literature review (SLR) examining how social media use and technology readiness enhance the marketing capabilities of fashion and tailoring SMEs. As digital platforms increasingly shape consumer behaviour and competition, many SMEs, particularly in the fashion and tailoring sectors, face challenges in adopting and optimising social media for marketing. Using a PRISMA-based review protocol, this research analysed peer-reviewed studies published between 2013 and 2024 across major academic databases. A total of selected articles meeting the inclusion criteria were synthesised through qualitative thematic analysis. The findings reveal three dominant themes: (1) social media functions as a strategic and cost-effective marketing tool that supports customer engagement, brand visibility, and product promotion; (2) technology readiness, comprising technological competence, digital infrastructure, and managerial support, significantly influences SMEs’ ability to adopt digital marketing tools; and (3) the integration of social media and adequate technology readiness strengthens SMEs’ marketing capabilities, particularly in market sensing, customer relationship management, and product differentiation. This review contributes theoretically by mapping the intersection between digital adoption and capability development, and practically by offering insights for SME practitioners and policymakers to support digital transformation in the fashion and tailoring industry.